Avaliação da qualidade de vida urbana dos condomínios horizontais da cidade de João Pessoa – PB - Lira, Anneliese Heyden Cabral de (2014)
This study is about the quality of urban life in the horizontal condominiums located in the city of João Pessoa – PB. This habitational type has been proliferating and substantially moving the local real estate market, using the premise that the “quality of life” inside the condominiums is supposedly higher than the urban standard found in the city outside its walls. However, there is no local researches that measures this so called “quality of life” by using specific and scientific methods. Thereby, based on the method “Index of the Quality of Urban Life in the city of João Pessoa” (IQUL-JP), the present study aims at filling that gap, dedicating itself to investigate the quality of life of the condominiums. Thus, the study subjects in this research were delimited by the use of criteria like demographic density, spatial dimension and location, configuring into three condominiums: Cabo Branco Residence Privé, Villas do Farol, and Alphaville. The main results in this research shows how important the location is on determining the quality of urban life, since the locational atributes translate the facilities and deficiencies of oportunities and urban access. In this sense, although the condominums analyzed have presented a high habitational and environmental quality, only the condominium Alphaville, which is located on a urban sector more connected to the consolidated urban network, has obtained a high index of quality of urban life. The condominiums Cabo Branco Residence Privé and Villas do Farol, which are located on the south sector of the city coast, presents low indexes of accesibility and urban facilities, due to the distance to the main and secondary centers, besides the deficient cover of public transportation, the considerable increase of the average time on the daily trips and the low quality on the provision of commerce and local services. The investigation also demonstrates that the quality of urban life measured does not match what is propagated by the advertising and the local real estate market, which gives high value to areas considered distant, with low urban density and physically and socially isolated.